Advances in intravesical therapy for urinary tract disorders. (2nd January 2016) - Tyagi, Pradeep; Kashyap, Mahendra; Hensley, Harvey; Yoshimura, Naoki
Abstract : Introduction : Intravesical therapy is a valuable option in the clinical management of urinary tract disorders such as interstitial cystitis/ painful bladder syndrome (IC/PBS) and refractory overactive bladder. This review will cover the latest advances in this field using polymer and liposomes as delivery platform for drugs, protein and nucleic acids. Areas covered : This review summarizes the significance of intravesical therapy for lower urinary tract disorders. The recent advancement of liposomes as a drug delivery platform for botulinum toxin, tacrolimus and small interfering RNA is discussed. The importance of polymers forming indwelling devices and hydrogels are also discussed, where all preparations improved efficacy parameters in rodent models. Clinical experience of treating IC/PBS with indwelling devices and liposomes are summarized and preclinical evidence about the downregulation of target gene expression in rodent bladder with liposomes complexed with siRNA is also reviewed. Expert opinion : There have been several advances in the field of intravesical therapy for improving clinical outcomes. One of the most promising research avenues is the repurposing of drugs, given previously by other routes of administration, such as tacrolimus. Intravesical therapy also opens up novel therapeutic targets with improved efficacy and safety for underactive bladder.